2003
DOI: 10.1136/jnnp.74.7.908
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous haemorrhage into metastatic brain tumours after stereotactic radiosurgery using a linear accelerator

Abstract: Objective: To determine the incidence and clinical characteristics of spontaneous haemorrhage into metastatic brain tumours after radiosurgery. Methods: Intratumour haemorrhage rate, clinical features, and treatment were evaluated in 54 patients with 131 brain metastases of varying origin who were treated using linear accelerator radiosurgery. The marginal dose was maintained constant at 20 or 25 Gy, irrespective of tumour size. Results: Haemorrhage was identified in 7.4% of the metastases (five tumours in fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 12 publications
0
22
0
2
Order By: Relevance
“…9,24 Recently, Suzuki, et al, 27 suggested that radiosurgery is a contributing factor for spontaneous intratumoral hemorrhage. They concluded that radiosurgery may cause the hemorrhages, which occur at relatively short intervals after treatment, and they proposed the following mechanisms: 1) thrombosis induced by cytokines produced by irradiated endothelial cells; 2) increase in intravascular outflow resistance due to radiation-induced venous obliteration; and 3) necrosis in the tumor and blood flow congestion in residual neoplastic tissue.…”
Section: Discussionmentioning
confidence: 98%
“…9,24 Recently, Suzuki, et al, 27 suggested that radiosurgery is a contributing factor for spontaneous intratumoral hemorrhage. They concluded that radiosurgery may cause the hemorrhages, which occur at relatively short intervals after treatment, and they proposed the following mechanisms: 1) thrombosis induced by cytokines produced by irradiated endothelial cells; 2) increase in intravascular outflow resistance due to radiation-induced venous obliteration; and 3) necrosis in the tumor and blood flow congestion in residual neoplastic tissue.…”
Section: Discussionmentioning
confidence: 98%
“…The only predisposing factor was GKRS performed 24 hours before presentation. Many cases of intratumoral or peritumoral hemorrhage in the literature were associated with meningiomas (33) or brain metastases (24,36). However, some bleeding was spontaneous, and GKRS cannot be the only cause of this complication.…”
Section: Discussionmentioning
confidence: 99%
“…The biological effect of SRS is early direct injury to the tumor cells and then late injury to the tumor vasculature within the high-dose target volume (24). Some of these effects can directly interfere with peripheral structures such as the nerves, vessels, and nuclei, whereas other side effects are indirectly caused by the immediate and slowly regressing tumor swelling which mechanically impinges on the same surrounding tissues (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 30-day period following SRS, most reported cases of postradiosurgery hemorrhage within 72 hours of radiosurgery occurred in patients with irradiated tumors. (Franco-Vidal et al 2007;Izawa et al 2006;Park et al 2000;Suzuki et al 2003;Uchino et al 2003) There is only one report of AVM hemorrhage within 72 hours following SRS. (Nataf et al 2004) Within 4 to 30 days following SRS there are a few more documented cases of post-radiosurgery AVM hemorrhage.…”
mentioning
confidence: 99%